Possible Worlds in Sam Shepard’s Fool for Love and Its Cinematic Adaptation - AMANI, Omid; PIRNAJMUDDIN, Hossein; Mohammad MARANDI, Seyed (Anafora, 2023)
This paper is an attempt to compare Sam Shepard’s Fool for Love, published in 1983, and its cinematic adaptation directed by Robert Altman, released in 1985, in terms of the notion of possible worlds (in the philosophically-oriented branch of cognitive poetics). In her discussion of possible worlds, Marie-Laure Ryan proposes a typology of accessibility relations (identity of properties, identity of inventory, compatibility of inventory, chronological, physical, taxonomic, logical, analytical, and linguistic compatibility) in order to account for how the sense of the reality of our actual world reverberates in fictional worlds. Ryan also offers another typology, that is, the internal structure of the fictional world (knowledge worlds, intention worlds, wish worlds, obligation worlds, and fantasy worlds) to show how the characters’ different conceptions of the world define and build up the narrative structure of fiction. It is argued that the change of medium – drama into film in this case – results in some changes in the possible worlds projected, since verbality and visuality give rise to some differences in terms of modes of perception. Also discussed is the significance in this regard of the spatio-temporal scope, which is confined in the case of drama, a genre often conceived to be performed, whereas in a movie the director is able to expand this scope as the occasion demands.